Applicability of automatic spectral domain optical coherence tomography for glaucoma mass screening - Nakano T (Dove Medical Press, 2016)
Tadashi Nakano,1 Takeshi Hayashi,2 Toru Nakagawa,2 Toru Honda,2 Satoshi Owada,3 Hitoshi Endo,3 Masayuki Tatemichi3 1Department of Ophthalmology, The Jikei University School of Medicine, Tokyo, 2Hitachi Health Care Center, Ibaraki, 3Department of Preventive Medicine, Tokai University, School of Medicine, Kanagawa, Japan Purpose: To perform a preliminary evaluation of the applicability of automatic spectral domain optical coherence tomography (ASD-OCT) for glaucoma mass screening in a population-based setting. Methods: Information using ASD-OCT (thicknesses of the macular retinal nerve fiber layer [mRNFL], disc retinal nerve fiber layer [dRNFL], ganglion cell layer [GCL] + inner plexiform layer [IPL]; GCL+, and ganglion cell complex [GCL + IPL + RNFL; GCL++]) was obtained from 245 eyes of 123 glaucomatous subjects and 1,454 eyes of 727 normal subjects. For all four measurements, each grid was scored as follows: 2= within 95% of the normal database; 1= within 5%; and 0= within 1%. The sums of each grid (mRNFLs, dRNFLs, GCL+s, and GCL++s) were used as indicators. The effectiveness was estimated by the area under the receiver operating characteristic curve (AUC-ROC). The appropriate algorithm was then applied to 10,145 eyes of 5,088 subjects from the general population (mean age: 50.1±10.3 years). Results: AUC-ROC of mRNFLs, dRNFLs, GCL+s, and GCL++s was 0.927 (95% confidence interval [CI] =0.903–0.950), 0.919 (95% CI =0.899–0.940), 0.972 (95% CI =0.958–0.986), and 0.972 (95% CI =0.957–0.986), respectively. The discriminant analysis demonstrated that the canonical correlation coefficients of mRNFLs, dRNFLs, GCL+s, and dGCL++s were 0.07, 0.255, 0.661, and 0.207, respectively. AUC-ROC of the discriminant value was 0.971 (95% CI =0.956–0.986). The sensitivity/specificity using GCL+s (cutoff =160) was 81.6%/99.9%. This algorithm was applied to the general population, and 1,658 eyes (16.3%) were found to be positive for glaucoma. Conclusion: In the case–control setting, ASD-OCT showed a relatively high performance, and the thickness of the GCL + IPL was the best predictor. However, further prospective studies are needed, in which the results of this study are compared to the general population, because the false-positive rate of glaucoma seems to be high. Keywords: automatic spectral domain optical coherence tomography, glaucoma mass screening, population based, applicability